Zimmermann-Laband Syndrome: Report of a Case with Early Cardiac Complications - Atul P Sattur; Krishna N Burde; Venkatesh G Naikmasur; Megha Goyal (Wolters Kluwer Medknow Publications, 2010)
Laband syndrome (LS) is a rare autosomal dominant inherited disorder characterized by coarse facial appearance, gingival fibromatosis, and hypoplasia of the terminal phalanges and nails of hands and feet. Additionally, more variable features include hyperextensibility of joints, hepatosplenomegaly, mild hirsutism, and mental retardation. This paper reports a case study of 22-year-old male exhibiting symptoms of Laband syndrome, including cardiac involvement described only in one other case. Detection and timely recognition of such syndrome associated with gingival fibromatosis allows adequate dental care and cardiac evaluation at periodic intervals is merited to prevent complications and improve the overall quality of life for these patients. Dental practitioners should be alert for developmental abnormalities that may occur in patients with gingival fibromatosis as this may indicate the presence of a rare disorder like Zimmermann-Laband syndrome. A comprehensive medical history and physical systemic evaluation are essential for correct diagnosis, treatment and prevention of cardiovascular complications in future in these patients.